(untitled) (European Journal of Teaching and Education, 2023)
In discussing the limits of human knowledge, physical objects are, in principle, not identical to the apparent ones. This is because the latter depend also on the observer. Virtual reality (VR) models are environments that address the senses and therefore belong to the apparent space. Therefore, they seem to prevent an epistemic justification. Based on that, this paper discusses VR technology’s potential to provide knowledge of external reality to students. This is particularly important in light of the conditions imposed by the COVID-19 pandemic, which have led to an increasingly significant role of VR related technologies in education. The research question of this study is whether VR models being used as educational tools, bring us closer – or not – to knowing the properties of physical objects. The main focus of this epistemic investigation is Russell’s theory of perception with an emphasis to the concept of space. Analysis indicates that VR is educationally useful especially when it comes to objects that are absent from our perceptual range. VR technology brings us closer to the theoretical properties of non-perceptual objects, those that cannot be perceived by the senses, like exoplanets. Furthermore, it brings us closer to the non-perceptual properties of directly perceived objects, properties referring, for example to subatomic structures. In a theoretical level, this macro and micro “terra incognita” may be linked to the sensibilia entities proposed by Russell (1914).